An analysis of radiographer preliminary image evaluation – A focus on common false negatives. Issue 3 (22nd March 2021) - Alexander‐Bates, Isobel; Neep, Michael J.; Davis, Benjamin; Starkey, Deborah
Abstract: Introduction: Preliminary image evaluation (PIE) is a mechanism whereby radiographers provide a preliminary evaluation of whether pathology is present in their radiographs, typically acquired within the emergency department (ED). PIE provides referrers with a timely communication of pathology prior to the availability of a radiology report. The purpose of this study was to determine the most common radiographer PIE false‐negative interpretations. Methods: Each month over a two‐year period, 100 PIEs of adult and paediatric patients were randomly reviewed in a metropolitan hospital ED. The radiographer's PIE was compared with the radiologist's report and categorised into basic quality indicators; true positive, true negative, false positive and false negative. The anatomical regions which most commonly indicated a false‐negative interpretation were further analysed. Results: 2402 cases were reviewed which resulted in an overall PIE accuracy of 88.7%. Wrists, hands, phalanges (upper), ankles, feet and phalanges (lower) reporting the highest false‐negative or false‐negative/true‐positive interpretations (60/116). Of the 60 false‐negative PIEs, 68 pathologies were identified. 41.1% (28/68) of the pathology not identified were in the phalanges. Within these regions, examinations with multiple injuries commonly reported false negatives (17/60). Conclusions: This study demonstrated the most common false‐negative radiographer PIEs were within the upper and lower distal extremities. Specifically, the phalanges and examinations demonstrating multiple injuries reported high levels of misinterpretation. The misinterpretation in multi‐injury examinations could be attributed to 'Subsequent Search Miss (SSM)' error. These results provide valuable insights into areas of emphasis when providing image interpretation education. Abstract : Preliminary image evaluation (PIE) is a mechanism, whereby radiographers provide a preliminary evaluation on whether pathology is present in the radiographs acquired, typically within the emergency department (ED). Over a two‐year period, 100 PIEs from a metropolitan hospital ED were audited and categorised into the basic quality indicators true positive, true negative, false positive and false negative. 2402 cases were reviewed, with wrists, hands, phalanges (upper), ankles, feet and phalanges (lower) reporting the highest false‐negative or true‐positive/false‐negative interpretations (60/116).